Association Between Nonsteroidal Antiinflammatory Drug Use and Adverse Clinical Outcomes Among Adults Hospitalized With Coronavirus 2019 in South Korea: A Nationwide Study. (27th July 2020) - Jeong, Han Eol; Lee, Hyesung; Shin, Hyun Joon; Choe, Young June; Filion, Kristian B; Shin, Ju-Young
Abstract: Background: Nonsteroidal antiinflammatory drugs (NSAIDs) may exacerbate coronavirus disease 2019 (COVID-19) and worsen associated outcomes by upregulating the enzyme that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) binds to in order to enter cells. Methods: We conducted a cohort study using South Korea's nationwide healthcare database, which contains data for all individuals who received a COVID-19 test (n = 69 793) as of 8 April 2020. We identified adults hospitalized with COVID-19, where cohort entry was the date of hospitalization. NSAID users were those prescribed NSAIDs in the 7 days before and including cohort entry, and nonusers were those not prescribed NSAIDs during this period. Our primary outcome was a composite of in-hospital death, intensive care unit admission, mechanical ventilation use, and sepsis; our secondary outcomes were cardiovascular complications and acute renal failure. We conducted logistic regression analysis to estimate odds ratio (OR) with 95% confidence intervals (CIs) using inverse probability of treatment weighting to minimize confounding. Results: Of 1824 adults hospitalized with COVID-19 (mean age, 49.0 years; female, 59%), 354 were NSAID users and 1470 were nonusers. Compared with nonuse, NSAID use was associated with increased risks of the primary composite outcome (OR, 1.54; 95% CI, 1.13–2.11) but insignificantly associated with cardiovascular complications (OR, 1.54; 95% CI, 0.96–2.48) or acute renal failure (OR, 1.45; 95% CI, 0.49–4.14). Conclusions: While awaiting the results of confirmatory studies, we suggest NSAIDs be used with caution for COVID-19 patients as the harms associated with their use may outweigh their benefits. Abstract : Nonsteroidal antiinflammatory drug (NSAID) use was associated with a 54% increased risk of a composite outcome (in-hospital death, intensive care unit admission, mechanical ventilation use, sepsis) compared with nonuse. We support the concern that NSAIDs may exacerbate coronavirus disease 2019.